Bacterial lipopolysaccharides form physically cross-linked, two-dimensional gels in the presence of divalent cations1. Issue 30 (14th August 2015) - Herrmann, Moritz; Schneck, Emanuel; Gutsmann, Thomas; Brandenburg, Klaus; Tanaka, Motomu
<x xml:space="preserve">Abstract</x> Interface rheology suggests bacteria blocks antibacterial peptides by forming physically cross-linked gels of lipopolysaccharides in the presence of divalent cations.